Answer:
Explanation:
The graph is a straight line graph.
The y axis is h(x) and the x axis is x
The equation of a straight line can be represented in the slope-intercept form, y = mx + c
Where c = intercept
Slope, m =change in value of y on the vertical axis / change in value of x on the horizontal axis
change in the value of y = y2 - y1
Change in value of x = x2 -x1
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
Looking at the graph
y2 = - 2
y1 = + 4
x2 = 2
x1 = 0
Slope, m = (- 2 - 4)/(2 - 0)
m = - 3
To determine the intercept, c, let us substitute m= - 3, y = - 2 and x = 2 into the slope intercept equation. It becomes
- 2 = - 3×2 + c
- 2 = - 6 + c
c = - 2 + 6 = 4
The equation becomes
h(x) = - 3x + 4
The y intercept is the point at which x = 0. Therefore, the y intercept is
y = -3×0 + 4
y = 4
So the y intercept is 4